Translocation t(11;14) is associated with adverse outcome in patients with newly diagnosed AL amyloidosis when treated with bortezomib-based regimens - Bochtler, Tilmann; Hegenbart, Ute; Granzow, Martin; Seckinger, Anja; Kimmich, Christoph; Goldschmidt, Hartmut; Ho, Anthony Dick; Hose, Dirk; Jauch, Anna; Schönland, Stefan (Journal of clinical oncology, 2015)
Purpose Bortezomib has become a cornerstone in the treatment of AL amyloidosis. In this study, we addressed the prognostic impact of cytogenetic aberrations for bortezomib-treated patients. Patients and Methods We analyzed a consecutive series of 101 patients with AL amyloidosis treated with bortezomib-dexamethasone as first-line treatment by interphase fluorescence in situ hybridization (iFISH). Patients were ineligible for high-dose chemotherapy, which would put them at risk for cardiac or renal failure, and thus represented a poor-risk group. Results Presence of t(11;14), versus its absence, was associated with inferior hematologic event-free survival (median, 3.4 v 8.8 months, respectively; P = .002), overall survival (median, 8.7 v 40.7 months, respectively; P = .05), and remission rate (≥ very good partial remission; 23% v 47%, respectively; P = .02). In multivariable Cox regression models incorporating established hematologic and clinical risk factors, t(11;14) was an independent adverse prognostic marker for hematologic event-free survival (hazard ratio, 2.94; 95% CI, 1.37 to 6.25; P = .006) and overall survival (hazard ratio, 3.13; 95% CI, 1.16 to 8.33; P = .03), but not for remission (≥ very good partial remission). Markedly, the multiple myeloma high-risk iFISH aberrations t(4;14), t(14;16), del(17p), and gain of 1q21 conferred no adverse prognosis in this bortezomib-dexamethasone-treated group. After backward variable selection, the final multivariable model was validated in a consecutive series of 32 patients treated with bortezomib, dexamethasone, and cyclophosphamide. Conclusion iFISH results are important independent prognostic factors in AL amyloidosis. In contrast to our recently published results with melphalan and dexamethasone standard therapy, bortezomib is less beneficial to patients harboring t(11;14), whereas it effectively alleviates the poor prognosis inherent to high-risk aberrations. Given the discrepant response to different treatment modalities, iFISH may help to guide therapeutic choices in these poor-risk patients requiring rapid hematologic response.